Non-fatal self-inflicted versus undetermined intent injuries: patient characteristics and incidence of subsequent self-inflicted injuries - Peterson, Cora (Inj Prev, 2018)
BACKGROUND: Non-fatal self-inflicted (SI) injuries may be underidentified in administrative medical data sources. OBJECTIVE: Compare patients with SI versus undetermined intent (UI) injuries according to patient characteristics, incidence of subsequent SI injury and risk factors for subsequent SI injury. METHODS: Truven Health MarketScan was used to identify patients’ (aged 10–64) first SI or UI injury in 2015 (index injury). Patient characteristics and subsequent SI within 1 year were assessed. A logistic regression model examined factors associated with subsequent SI. RESULTS: Among analysed patients (n=44 806; 36% SI, 64% UI), a higher proportion of patients with SI index injury were female, had preceding comorbidities (eg, depression), Medicaid (vs commercial insurance), treatment in an ambulance or hospital and cut/pierce or poisoning injuries compared with patients with UI index injury. Just 1% of patients with UI had subsequent SI≤1 year vs 16% of patients with SI. Among patients with UI index injury, incidence of and risk factors for subsequent SI injury were similar across assessed age groups (10–24 years, 25–44 years, 45–64 years). Severe injuries (eg, treated in emergency department), cut/pierce or poisoning injuries, mental health and substance use disorder comorbidities and Medicaid (among adult patients) were risk factors for subsequent SI among patients with UI index injuries. CONCLUSIONS: Regardless of circumstances that influence clinicians’ SI vs UI coding decisions, information on incidence of and risk factors for subsequent SI can help to inform clinical treatment decisions when SI injury is suspected as well as provide evidence to support the development and implementation of self-harm prevention activities.